Sarcasm in I’m Glad My Mom Died by Jennette McCurdy and Its Bahasa Indonesia Translation - Haya Jaida Istiqomah; O. Djuharie Setiwan; Agry Paramitha (Universitas Islam Negeri Palopo, 2025)
In the era of globalization translation has become more important. Humans have even created translation machines to connect people from around the world. However, translator machines are different from human living translators. The sense of one culture cannot be translated by machine. That is why translators are important. This research aims to find out the translation technique used to translate the sarcasm found in the memoir entitled I’m Glad My Mom Died (2022) by Jennette McCurdy. This research used John Dryden’s translation technique to analyse the translation of the sarcasm of the memoir. There are three translation techniques according to Dryden (in Munday, 2002); metaphrase, paraphrase, and imitation. This study also analyzed the types of sarcasm that are found in the memoir based on Camp (2012); like-prefixed, propositional, lexical, and illocutionary. The researchers of this study found 11 sarcasms from the memoir. The 11 data of sarcasm in the book align with the types of sarcasm outlined by Camp (2012). The researcher found four types of sarcasm in the memoir and each of the sarcasms were translated with different techniques. The use of different techniques for each sarcasm is to make it easier for the target audience to understand and to not lose the sarcasm essence from the memoir.